Table of Contents
Last modified on February 12th, 2025
A system of linear equations is a set of 2 or more linear equations involving the same set of variables.
Together, they are called a system of linear equations.
Similarly,
These equations represent straight lines in a coordinate system, and their solutions correspond to points where these lines intersect.
The general form of a linear equation in n variables is expressed as:
a11x1 + a12x2 + … + a1nxn = b1
a21x1 + a22x2 + … + a2nxn = b2
… … … … … … …
an1x1 + an2x2 + … + annxn = bn
Here,
The solutions to a system are the values of x1, x2, … that satisfy all equations simultaneously.
A system of linear equations normally has a single solution, but sometimes, it can have no solution or infinite solutions depending on the relationship between the equations. We can verify these solutions either algebraically or graphically:
A system is said to have a unique solution if it has exactly one solution. This occurs when the equations represent two lines that intersect at a single point.
For example, the system 2x + y = 5, x – y = 1 has the solution (2, 1)
A system has no solution if the equations represent parallel lines and thus can never intersect.
For example, the system 2x + y = 3, 4x + 2y = 8 has no solution
A system has infinitely many solutions when a system of equations is represented by the same line, which means every point on the line is a solution.
For example, 2x + 4y = 8, x + 2y = 4 are identical, and thus the system has infinitely many solutions.
We use different methods to solve a system of linear equations. It depends on the complexity of the system and the way we want to solve it.
This method provides a visual way to find the solution. Each equation is plotted as a straight line on a coordinate plane. The point where the lines intersect represents the solution to the system.
Let us consider the system:
y = 2x + 1 …..(i)
y = -x + 4 …..(ii)
Step 1: Graphing the First Equation
From equation (i),
y = 2x + 1
Here, the slope m is 2, and the y-intercept c is 1
Thus, the coordinates of the y-intercept are (0, 1)
Now, using the slope and y-intercept, we get
x | 2x + 1 | y |
---|---|---|
-1 | 2(-1) + 1 | -1 |
0 | 2(0) + 1 | 1 |
1 | 2(1) + 1 | 3 |
After plotting these points, we get
Step 2: Graphing the Second Equation
From equation (ii),
y = -x + 4
Here, the slope m is -1, and the y-intercept c is 4
Thus, the coordinates of the y-intercept are (0, 4)
Now, using the slope and y-intercept, we get
x | -x + 4 | y |
---|---|---|
-1 | -(-1) + 4 | 5 |
0 | -(0) + 4 | 4 |
1 | -(1) + 4 | 3 |
After plotting these points, we get
Step 3: Identifying the Intersection Point
Now, observing the graphs of these two lines, we conclude
The two lines intersect at (1, 3).
This means the solution to the system is x = 1 and y = 3
Here, since two lines intersect at one point (1, 3), the given system has one unique solution.
Note: Graphing may not always give accurate solutions, especially when working with decimals or fractions.
Determine the nature of the system:
As we can observe, the lines have one intersection point on the graph.
They have one unique solution.
Thus, the system is consistent and independent.
In this method, we solve one equation for a variable in terms of the other and substitute it into the second equation. This transforms the system into a single equation with one variable which makes the system easier to solve. Once we find the value of the first variable, we substitute it back into the original equation to determine the second variable.
Let us consider the system:
x + y = 6 …..(i)
2x – y = 3 …..(ii)
Step 1: Solving for one variable in Terms of the Other
First, we solve for x in terms of y.
From equation (i),
x = 6 – y …..(iii)
Step 2: Substituting
Now, substituting (iii) into the equation (ii),
2(6 – y) – y = 3
⇒ 12 – 2y – y = 3
⇒ 12 – 3y = 3
⇒ 3y = 12 – 3
⇒ 3y = 9
⇒ y = 3
Step 3: Solving for x
Substituting y = 3 back into (iii), we get
x = 6 – 3
⇒ x = 3
Thus, the solution is x = 3 and y = 3
Solve the following linear equations by substitution:
2x + 3y = 18
4x + 2y = 22
Given,
2x + 3y = 18 …..(i)
4x + 2y = 22 …..(ii)
From equation (i),
2x + 3y = 18
⇒ 2x = 18 – 3y
⇒ x = ${\dfrac{18-3y}{2}}$ …..(iii)
Substituting (iii) into the equation (ii),
${4\left( \dfrac{18-3y}{2}\right) +2y=22}$
⇒ ${2\left( 18-3y\right) +2y=22}$
⇒ ${\dfrac{2\left( 18-3y\right) }{2}+\dfrac{2y}{2}=\dfrac{22}{2}}$
⇒ ${18-3y+y=11}$
⇒ ${18-2y=11}$
⇒ ${2y=18-11}$
⇒ ${2y=7}$
⇒ ${y=\dfrac{7}{2}}$
Substituting ${y=\dfrac{7}{2}}$ back into (iii),
${x=\dfrac{18-3y}{2}}$
⇒ ${x=\dfrac{18-3\left( \dfrac{7}{2}\right) }{2}}$
⇒ ${x=\dfrac{18-\dfrac{21}{2}}{2}}$
⇒ ${x=\dfrac{36-21}{4}}$
⇒ ${x=\dfrac{15}{4}}$
Thus, ${x=\dfrac{15}{4}}$ and ${y=\dfrac{7}{2}}$
This method involves adding or subtracting the given equations to eliminate one variable, simplifying the system into a single equation with one variable. Once we solve for that variable, we substitute its value back into one of the original equations to find the remaining variable(s).
Let us consider the system:
3x + 2y = 12 …..(i)
5x – 2y = 8 …..(ii)
Step 1: Adding the Equations
(3x + 2y) + (5x – 2y) = 12 + 8
⇒ 3x + 2y + 5x – 2y = 20
Step 2: Simplifying
⇒ 3x + 5x = 20
⇒ 8x = 20
⇒ x = ${\dfrac{20}{8}}$
⇒ x = ${\dfrac{5}{2}}$
Step 3: Substituting
Substituting x = ${\dfrac{5}{2}}$ back into equation (i), we get
⇒ ${3\left( \dfrac{5}{2}\right) +2y=12}$
⇒ ${\dfrac{15}{2}+2y=12}$
⇒ ${2y=12-\dfrac{15}{2}}$
⇒ ${2y=\dfrac{24-15}{2}}$
⇒ ${2y=\dfrac{9}{2}}$
⇒ ${y=\dfrac{9}{4}}$
Thus, the solution is x = ${\dfrac{5}{2}}$ and ${y=\dfrac{9}{4}}$
What is the solution to this system of linear equations? (Use elimination method)
4x + 3y = 20
2x – 3y = 4
Given,
4x + 3y = 20 …..(i)
2x – 3y = 4 …..(ii)
Adding the equations (i) and (ii),
(4x + 3y) + (2x – 3y) = 20 + 4
⇒ 4x + 3y + 2x – 3y = 24
⇒ 4x + 2x = 24
⇒ 6x = 24
⇒ x = 4
Substituting x = 4 into equation (i),
4x + 3y = 20
⇒ 4(4) + 3y = 20
⇒ 16 + 3y = 20
⇒ 3y = 4
⇒ y = ${\dfrac{4}{3}}$
Thus, x = 4 and y = ${\dfrac{4}{3}}$
The inverse matrix method is particularly useful for solving complex or larger systems of linear equations. In this approach, the system is rewritten in matrix form as:
AX = B
To solve the system, we find the matrix X, which represents the values of the unknowns.
Here,
The solution can be found using the formula:
Note: Since A-1 exists, A is an invertible matrix.
Now, let us solve the system of linear equations:
2x + 3y = 8 …..(i)
4x + y = 5 …..(ii)
Step 1: Expressing the System in Matrix Form
To organize the equations in a standard way, we rewrite the equations (i) and (ii) in the matrix form as:
AX = B
⇒ ${\begin{bmatrix} 2 & 3 \\ 4 & 1 \end{bmatrix}\begin{bmatrix} x \\ y \end{bmatrix}=\begin{bmatrix} 8 \\ 5 \end{bmatrix}}$
Step 2: Finding the Inverse of Matrix A
To compute the inverse matrix of A, we first find the determinant A. If A is invertible (i.e., whether an inverse matrix exists):
Now, for the given matrix A = ${\begin{bmatrix} 2 & 3 \\ 4 & 1 \end{bmatrix}}$,
det(A) = (2)(1) – (3)(4) = 2 – 12 = -10 ≠ 0, the inverse exists.
Since the inverse of a 2 × 2 matrix A = ${\begin{bmatrix} a & b \\ c & d \end{bmatrix}}$
A-1 = ${\dfrac{1}{\det \left( A\right) }\begin{bmatrix} d & -b \\ -c & a \end{bmatrix}}$, where det(A) = (ad – bc)
⇒ A-1 = ${\dfrac{1}{-10}\begin{bmatrix} 1 & -3 \\ -4 & 2 \end{bmatrix}}$ = ${\begin{bmatrix} -0.1 & 0.3 \\ 0.4 & -0.2 \end{bmatrix}}$
Step 3: Multiplying A−1 by B to Find X
Thus, by calculating the variable matrix, we get
X = A-1B
⇒ ${\begin{bmatrix} x \\ y \end{bmatrix}=\begin{bmatrix} -0.1 & 0.3 \\ 0.4 & -0.2 \end{bmatrix}\begin{bmatrix} 8 \\ 5 \end{bmatrix}}$
Multiplying the matrices, we get
x = (-0.1 × 8) + (0.3 × 5) = -0.8 + 1.5 = 0.7
y = (0.4 × 8) + (-0.2 × 5) = 3.2 – 1 = 2.2
Thus, the solution to the system is x = 0.7 and y = 2.2
The Gaussian elimination method is often used for larger systems with three or more equations. It involves converting the system into row echelon form and then using back-substitution to find the variable values.
Let us solve the system of equations:
2x + y – z = 8 …..(i)
-3x – y + 2z = -11 …..(ii)
-2x + y + 2z = -3 …..(iii)
Step 1: Converting the System of Equations into an Augmented Matrix
To organize the equations systematically, we express the system as an augmented matrix. It is a matrix where the column of constants is added to the right side of the coefficient matrix.
${\left[\begin{array}{ccc|c}2 & 1 & -1 & 8 \\-3 & -1 & 2 & -11 \\-2 & 1 & 2 & -3\end{array}\right]}$
Step 2: Forwarding Elimination to Convert to Row Echelon Form
To find a solution for one variable, we eliminate the values of the other variables by replacing the rows of the augmented matrix.
Here, we create zeros below the main diagonal, converting the matrix into an upper triangular form.
By replacing rows into the forms:
${R_{2}\leftarrow R_{2}+\dfrac{3}{2}R_{1}}$
${R_{3}\leftarrow R_{3}+R_{1}}$
After performing these operations, we get
${\left[\begin{array}{ccc|c}2 & 1 & -1 & 8 \\0 & 0.5 & 0.5 & -7 \\0 & 2 & 1 & 5\end{array}\right]}$
Eliminating values until we reach row echelon form,
${\left[\begin{array}{ccc|c}2 & 1 & -1 & 8 \\0 & 2 & 1 & 5 \\0 & 0 & 1 & -1\end{array}\right]}$
Step 3: Back-Substituting to Solve for Variables
If we have the system in upper triangular form, we solve for variables starting from the last row,
From the last row,
z = -1
Substituting z = -1 into the second row,
2y + (-1) = 5
⇒ 2y = 6
⇒ y = 3
Substituting y = 3 and z = -1 into the first row,
2x + 3 – (-1) = 8
⇒ 2x + 4 = 8
⇒ x = 2
Thus, the solution is (x, y, z) = (2, 3, -1)
This method is used when the system of equations has the same number of equations as unknowns, and the determinant of the coefficient matrix is nonzero.
To solve a system of n linear equations with n variables, we use the formula:
${x_{i}=\dfrac{\det \left( A_{i}\right) }{\det A}}$
Here,
Let us solve the equations:
2x + 3y = 5 …..(i)
4x – y = 1 …..(ii)
Step 1: Expressing the System in Matrix Form
In this method, we first express the system in organized matrix form AX = B
Here,
A = ${\begin{bmatrix} 2 & 3 \\ 4 & -1 \end{bmatrix}}$, X = ${\begin{bmatrix} x \\ y \end{bmatrix}}$, and B = ${\begin{bmatrix} 5 \\ 1 \end{bmatrix}}$
Step 2: Calculating the Determinant of A
Here,
det(A) = (2)(-1) – (3)(4) = -2 – 12 = -14
Note: For a 3 × 3 matrix, the determinant is found using expansion:
det(A) = ${a_{11}\begin{vmatrix} a_{22} & a_{23} \\ a_{32} & a_{33} \end{vmatrix}-a_{12}\begin{vmatrix} a_{21} & a_{23} \\ a_{31} & a_{33} \end{vmatrix}+a_{13}\begin{vmatrix} a_{21} & a_{22} \\ a_{31} & a_{32} \end{vmatrix}}$
Step 3: Calculating the Determinants of Modified Matrices Ax and Ay
Here, we replace columns to isolate the effect of each variable on the final solution.
To find x, we replace the first column of A with B:
Ax = ${\begin{bmatrix} 5 & 3 \\ 1 & -1 \end{bmatrix}}$
Thus, det(Ax) = (5)(-1) – (3)(1) = -5 – 3 = -8
To find y, replace the second column of A with B:
Ay = ${\begin{bmatrix} 2 & 5 \\ 4 & 1 \end{bmatrix}}$
Thus, det(Ay) = (2)(1) – (5)(4) = 2 – 20 = -18
Step 4: Calculating the Values of x and y
By using Cramer’s Rule, we get
x = ${\dfrac{\det \left( A_{x}\right) }{\det A}}$ = ${\dfrac{-8}{-14}}$ = ${\dfrac{4}{7}}$
y = ${\dfrac{\det \left( A_{y}\right) }{\det A}}$ = ${\dfrac{-18}{-14}}$ = ${\dfrac{9}{7}}$
Thus, the solutions are: x = ${\dfrac{4}{7}}$ and y = ${\dfrac{9}{7}}$
Solve using the inverse matrix method:
2x + 3y = 8
4x – y = 2
Given,
2x + 3y = 8 …..(i)
4x – y = 2 …..(ii)
Step 1: Expressing the System in Matrix Form
The given system can be written as:
AX = B
⇒ ${\begin{bmatrix} 2 & 3 \\ 4 & -1 \end{bmatrix}\begin{bmatrix} x \\ y \end{bmatrix}=\begin{bmatrix} 8 \\ 2 \end{bmatrix}}$
Here,
A = ${\begin{bmatrix} 2 & 3 \\ 4 & -1 \end{bmatrix}}$
X = ${\begin{bmatrix} x \\ y \end{bmatrix}}$
B = ${\begin{bmatrix} 8 \\ 2 \end{bmatrix}}$
Step 2: Finding the Inverse of Matrix A
Calculating det(A), we get
det(A) = (2)(-1) – (3)(4) = -2 – 12 = -14
Since det(A) ≠ 0, the inverse exists.
Now, calculating A-1, we get
${A^{-1}=\dfrac{1}{\det \left( A\right) }\cdot adj\left( A\right)}$
⇒ ${A^{-1}=\dfrac{1}{-14}\begin{bmatrix} 1 & -3 \\ -4 & 2 \end{bmatrix}=\begin{bmatrix} \dfrac{1}{14} & \dfrac{3}{14} \\ \dfrac{4}{14} & \dfrac{-2}{14} \end{bmatrix}}$
Step 3: Solving for X
Since AX = B
⇒ X = A-1B
⇒ X = ${\begin{bmatrix} \dfrac{1}{14} & \dfrac{3}{14} \\ \dfrac{4}{14} & -\dfrac{2}{14} \end{bmatrix}\begin{bmatrix} 8 \\ 2 \end{bmatrix}}$
⇒ X = ${\begin{bmatrix} \dfrac{1}{14}\times 8+\dfrac{3}{14}\times 2 \\ \dfrac{4}{14}\times 8-\dfrac{2}{14}\times 2 \end{bmatrix}}$
⇒ X = ${\begin{bmatrix} \dfrac{14}{14} \\ \dfrac{28}{14} \end{bmatrix}}$
⇒ X = ${\begin{bmatrix} 1 \\ 2 \end{bmatrix}}$
Thus, the solutions are: x = 1 and y = 2
Last modified on February 12th, 2025